2019
DOI: 10.1002/jgh3.12197
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective investigation of tacrolimus combined with an anti‐tumor necrosis factorα antibody as remission induction therapy for refractory ulcerative colitis: Efficacy, safety, and relapse rate

Abstract: Background and AimCombined therapy with tacrolimus (TAC) and an anti‐tumor necrosis factorα (TNFα) antibody is used to induce remission in ulcerative colitis (UC) patients who have not responded to monotherapy with either drug. We evaluated the efficacy and safety of combined therapy, as well as the relapse rate.MethodsCombined therapy was performed to induce remission in UC patients showing an inadequate response to monotherapy with TAC or an anti‐TNFα antibody. The following items were assessed retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The problem with elderly UC patients, as already reported, is that the prognosis of emergency surgery is extremely poor. 10,11) In addition, it has been reported that the post-operative complication rate of pouchitis is around 50%, 12) and the symptoms such as diarrhea and fever continue after surgery, which may have an adverse effect on daily life. Based on the above, to avoid the risks associated with colectomy, especially the emergency surgery, and postoperative complications, the remission induction therapy with higher therapeutic effect is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The problem with elderly UC patients, as already reported, is that the prognosis of emergency surgery is extremely poor. 10,11) In addition, it has been reported that the post-operative complication rate of pouchitis is around 50%, 12) and the symptoms such as diarrhea and fever continue after surgery, which may have an adverse effect on daily life. Based on the above, to avoid the risks associated with colectomy, especially the emergency surgery, and postoperative complications, the remission induction therapy with higher therapeutic effect is needed.…”
Section: Introductionmentioning
confidence: 99%